Superior performance improvements in elite cyclists following short-interval vs effort-matched long-interval training - Rønnestad, B. R.; Hansen, J.; Nygaard, H.; Lundby, C. (Scandinavian Journal of Medicine & Science in Sports, 2020)
The purpose of this study was to compare the effects of 3 weeks with three weekly sessions (ie, nine sessions in total) of short intervals (SI; n = 9; 3 series with 13 × 30-second work intervals interspersed with 15-second recovery and 3-minutes recovery between series) against effort-matched (rate of perceived effort based) long intervals (LI; n = 9; 4 series of 5-minute work intervals with 2.5-minutes recovery between series) on performance parameters in elite cyclists (VO2max 73 ± 4 mL min-1 kg-1). There were no differences between groups in total volume and intensity distribution of training during the intervention period. SI achieved a larger (P < .05) relative improvement in peak aerobic power output than LI (3.7 ± 4.3% vs -0.3 ± 2.8%, respectively), fractional utilization of VO2max at 4 mmol L-1 [La-] (3.0 ± 5.8 percent points vs -3.5 ± 2.7 percent points, respectively), and larger relative increase in power output at 4 mmol L-1 [La-] (2.0 ± 6.7% vs -2.8 ± 3.4, respectively), while there was no group difference in change of VO2max. Improvements in performance measured as mean power output during 20-minute cycling test were greater (P < .01) in SI compared with LI (4.7 ± 4.4% vs -1.4 ± 2.2%, respectively). Mean effect size of the improvement in the above variables revealed a small to large effect of SI training vs LI training. The data thus demonstrate that the present SI protocol induces superior training adaptations compared with the present LI protocol in elite cyclists.